CARDIOGENESIS CHANGES UNDER THE IMPACT OF CADMIUM CHLORIDE IN RAT EMBRYOGENESIS - Nefodova, O.O.; Shatorna, V.F.; Halperin, O.I.; Nefodov, O.O.; Yеroshenko G.A.; Tverdokhlib, I.V.; Harets, V.I. (World of Medicine and Biology, 2019)
The purpose of the experimental study was to determine the impact of cadmium chloride on the overall course of cardiogenesis with intragastric administration throughout the entire pregnancy period in rats. Experimental studies were carried out on female Wistar rats. To simulate the effect of cadmium chloride throughout the pregnancy, Wistar female rats were daily administered the aqueous solution of cadmium chloride per os via a probe at the dose of 1.0 mg/kg. The cardiofetal index growing in the group of exposure to cadmium chloride indicates an increase in the cardiac weight in the group when the embryo body weight is reduced due to intoxication. Microscopically, in 12.3% of rats the atrium endocardium hyperplasia was detected in the group exposed to cadmium chloride at the indicated dose. In 26-29% of rats cadmium chloride also led to changes in the formation of the embryo heart ventricles wall: thickening of both the compact and trabecular myocardium layers and the formation of abnormal forms of trabeculas.